STRATEGI PEMERINTAH DAERAH DALAM MENGATASI ANAK PUTUS SEKOLAH (ATS) DI WILAYAH KABUPATEN KOTAWARINGIN TIMUR: Local Government Strategy in Addressing Dropouts (ATS) in East Kotawaringin District - Luci Dian Andayani; Muhamad Yusuf; Mambang Mambang; Nicodemus R Toun (Pencerah Publik, 2021)
This study aims to explore the phenomenon of the number of children dropping out of school and analyze the inhibitory factors of local government strategies in addressing dropouts (ATS) in The East Kotawaringin Region. In this research opportunity conducted qualitative analysis approach using descriptive approach shown to describe existing phenomena. That is based on the range and depth that the data collection in this study obtained from observations, interviews and documentation. The documents related to the research are data on handling ATS in the form of technical instructions (juknis), standard norms of procedures and criteria (NSPK), guidelines, as well as the results of data collection and implementation of activities by field personnel dikmas (TLD) as research materials. The results showed that the strategy to anticipate and handle ATS in east Kotawaringin district, local government with BAPPEDA as coordinator, coordinating the Education Office in the implementation of activities to handle dropouts by coordinating and synergizing with TLD officers in the implementation of ATS data collection in East Kotawaringin. Persuasive approach from field officers, making school-age children who are not school-age (ATS) who are successfully recorded willing to return to study either through formal channels (schools) or through nonformal institutions such as Learning Centers (SKB), Community Learning Activity Centers (PKBM), and Institutes of Courses and Training (LKP).